The Crvenka loess-paleosol sequence: A record of continuous grassland domination in the southern Carpathian Basin during the Late Pleistocene - Markovic, Slobodan B.; Sumegi, Pal; Stevens, Thomas; Schaetzl, Randall J.; Obreht, Igor; Chu, Wei; Buggle, Bjorn; Zech, Michael; Zech, Roland; Zeeden, Christian; Gavrilov, Milivoj B.; Peric, Zoran; et al. (ELSEVIER, 2018)
In this study, we compare two independent paleoenvironmental proxies for a loess sequence in northern Serbia, in the southern Carpathian Basin: novel n-alkane biomarkers and traditional land snail assemblages. Both are associated with other, more widely used proxy data for loess sections, such as environmental magnetism, grain size, and geochemical indices. Together, these paleoenvironmental proxy records provide evidence for the continued dominance of grasslands during the Late Pleistocene in the Southern Carpathian Basin. It is contrary to other European loess provinces, which are characterized by high diversity of Late Pleistocene environments (ranging from tundra-like to deciduous forest habitats). These findings highlight the southeastern part of Carpathian Basin as an important, but still insufficiently investigated, biogeographical refugium, and biodivarsity preservation zone. The reason for this is a mostly stable paleoclimate for much of the Late Pleistocene.